2019
DOI: 10.2134/agronj2019.04.0280
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture Increases Yields and Economic Returns of Potato, Forage, and Grain Systems of the Andes

Abstract: Physical and environmental vulnerability analysis conducted for the Illangama watershed located in Ecuador's Andean highlands, shows deteriorated soil quality and declining crop productivity. These problems are caused by soil erosion in steep slopes and inappropriate soil management practices. Research projects conducted from 2011 to 2014 adopted and examined the feasibility of conservation agriculture practices for potato (Solanum tuberosum L.), oat (Avena sativa L.) and vetch (Vicia sativa L.), barley (Horde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…No‐till practices, which reduce mechanical soil disturbance to an absolute minimum, can have important economic and environmental benefits (e.g., reduced field operations, reduced erosion, retention of nutrient‐rich top soil, improved water capture and retention) (Delgado et al., 2019; Hobbs et al., 2007; Mosquera et al., 2019), yet the yield impacts of no‐till are nuanced and context dependent, as well as dependent on management duration (Daigh et al., 2018; Nouri et al., 2020). There is evidence of near‐ and long‐term yield reductions with no‐till in some cropping systems (Giller et al., 2015; Pittelkow et al., 2015a; Rusinamhodzi et al., 2011).…”
Section: Minimizing Soil Disturbance (No‐till) and Crop Yieldsmentioning
confidence: 99%
“…No‐till practices, which reduce mechanical soil disturbance to an absolute minimum, can have important economic and environmental benefits (e.g., reduced field operations, reduced erosion, retention of nutrient‐rich top soil, improved water capture and retention) (Delgado et al., 2019; Hobbs et al., 2007; Mosquera et al., 2019), yet the yield impacts of no‐till are nuanced and context dependent, as well as dependent on management duration (Daigh et al., 2018; Nouri et al., 2020). There is evidence of near‐ and long‐term yield reductions with no‐till in some cropping systems (Giller et al., 2015; Pittelkow et al., 2015a; Rusinamhodzi et al., 2011).…”
Section: Minimizing Soil Disturbance (No‐till) and Crop Yieldsmentioning
confidence: 99%
“…With conservation agriculture we may be able to increase economic returns, increase yields, reduce the potential for erosion, and potentially adapt to a changing climate and more frequent extreme events that may lead to increased erosion. Recent studies on conservation agriculture (no-till, crop residue management, and cover crops, with nitrogen [N] fertilizer) have shown that cover crops can contribute to increased yields and economic returns in tropical highlands in an Andean region (Barrera et al, 2019;Delgado et al, 2019).…”
Section: Challenges For Tropical Regionsmentioning
confidence: 99%
“…The Andean region of South America is a region impacted by cultivation, which is increasing the potential for soil erosion since large areas of the cultivated soils are under slopes that have high erosion potential (Barrera et al, 2019;Delgado et al, 2019;Monar et al, 2013;Figs. 4 and 5).…”
Section: New Cover Crops Residue Management and No-till Systemmentioning
confidence: 99%
See 2 more Smart Citations